TARI BARIS DADAP DALAM KONTEKS SOSIAL-RELIGIUS MASYARAKAT DESA CEMPAGA, KECAMATAN BANJAR, KABUPATEN BULELENG (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
This study explores the baris dadap dance as a sacred art form of the Bali Aga community inCempaga Village, Banjar District, Buleleng Regency. The dance functions not only as anartistic expression but also as a religious, social, and cultural medium embedded within thecommunity’s spiritual and customary systems. Using a qualitative approach, this researchanalyzes three main aspects: the mythological and religious foundations of the dance, its socialand structural functions, and its impact on the local economy and religious tourism. Findingsshow that the baris dadap dance plays a vital role in maintaining harmony among humans,nature, and ancestral spirits, while also strengthening community solidarity through thetransmission of values and ritual practices. Moreover, the dance contributes to local economicgrowth through active participation in community-based cultural and spiritual tourism. Thesefindings affirm that the baris dadap dance serves as an adaptive and relevant means of culturalpreservation, symbolizing the cultural resilience of the Bali Aga identity amid changing times.
Keywords: baris dadap dance, bali aga, cempaga village, sacredness, cultural preservation